Gene structure of human CD59 and demonstration that discrete mRNAs are generated by alternative polyadenylation. - Tone, M; Walsh, L; Waldmann, H (1992)
We have isolated the CD59 gene from human genomic libraries. The gene is distributed over more than 27 x 10(3) base-pairs and consists of one 5'-untranslated exon and three coding exons. The gene structure is similar to that of mouse Ly-6 with the exception of the larger size of CD59 introns. Northern blot analysis using six different probes located in the 3'-region of the gene shows that more than four different CD59 mRNA molecules are generated by alternative polyadenylation. Three of these polyadenylation sites were predicted from previously published cDNA sequences. We have isolated a fourth from Jurkat poly(A)+ RNA by the procedure of rapid amplification of cDNA ends. Alternative polyadenylation may be due to the RNA secondary structure around the typical polyadenylation signal, AAUAAA.